Posisi Nabi Muhammad Sebagai Komunikator Perspektif Al-Qur’an - Ali Mahfudz (STIU Al-Mujtama Pamekasan, 2021)
This article describes the position of the Prophet Muhammad SAW as a communicator in the perspective of the Qur'an which is a designation from Allah SWT. This shows that the Prophet Muhammad SAW is an ideal patron communicator who can serve as a role model in communication. Some of the terms communicators carried by the Prophet Muhammad SAW in the Qur'an include da>in, muballigh, mubayyin, mubashshir, mundhir, mudhakkir, muallim, dan murabbin. These terms will be explained by referring to the meaning of the language, terms, and their usage in the al-Qur'an. Keywords: Communication, Communicator, Prophet Muhammad SAW